Servant Leadership in International Education - David B. Austell (Journal of Global Initiatives, 2010)
The objective of "Servant Leadership in International Education" is to explore goodness of fit between Servant Leadership models, stemming primarily from the business and corporate communities (including such organizations as Southwest Airlines), and the service environments of International Education. The article will define the elements of Servant Leadership in its review of the key literature (for example Robert Greenleaf, Barbara Kellerman, John Maxwell, James MacGregor Burns, James Kouzes and Barry Posner, John Gardner, Peter Senge, Warren Bennis, and Margaret Wheatley). The article will define the service areas of International Education, and show strong goodness of fit between the elements of servant leadership and international education. Also, a discussion of cultural challenge-areas will be included.